The use of the Modified Early Obstetric Warning System (MEOWS) in women after pregnancies: a descriptive study - Schuler,Luciana (2019)
Abstract Objectives: to evaluate the modified early obstetric warning system (MEOWS) in women after pregnancies in a tertiary hospital in Brazil. Methods: a descriptive study was conducted with 705 hospitalized women. Vital signs (systolic and diastolic blood pressure, heart rate, respiratory rate, temperature) and lochia were registered on medical records and transcribed into the MEOWS chart of physiological parameters. On this graphic chart, yellow alerts were used to present moderate abnormalities in vital signs, while severe abnormalities were presented in red. The presence of at least one red alert or two yellow alerts were triggered to indicate the need for medical evaluation. Results: although abnormalities were found in the physiological parameters of 49.8% of the women identified from MEOWS triggers, medical evaluation was only requested for three patients (0.8%). Conclusions: in a retrospective application of the use of MEOWS showed a significant number of patients had triggered in which the nursing team did not recognize 99.2% of cases. This finding could be attributed to the fact that MEOWS has not been yet adopted in this service as part of the nursing care. The application of this tool would result in a better care because critical situations would be recognized and corrected quickly, avoiding unfavorable outcomes.